Evaluation of a novel dipotassium phosphate bolus for treatment of metabolic disorders in dairy cattle - Walter Verhoef; Sjoert Zuidhof; Joseph A. Ross; Kendall Beaugrand; Merle Olson (Frontiers in Veterinary Science, 2023)
A dipotassium phosphate bolus (K Phos-Boost) has been developed to treat both hypophosphatemia and hypokalemia, as the clinical signs of both conditions are similar and occur in the early post-partum period. The objective of this research was to evaluate the efficacy and application of the bolus for prevention and treatment of metabolic diseases that are common in dairy production systems. Study 1 (Pharmacokinetic study): Healthy post-partum cows were either untreated or received two K Phos-Boost boluses at times 0, 24, and 48 h. Blood was taken at t = 0, 2-, 4-, 6-, 8-, 10-, 24-, and 52-h post-treatment for analysis of total serum minerals. There was an increase in serum phosphorous to normal levels within 2 h of treatment with the bolus, but control cows remained hypophosphatemic. Serum potassium was significantly elevated 2 h after bolus administration relative to control, while calcium, magnesium, sodium, and chloride levels were not affected by the K Phos-Boost bolus. Study 2 (Downer Cow Treatment): K Phos-Boost boluses were provided to cows that were unresponsive to intravenous calcium therapy and had been unable to stand for over 24 h (“downer cows”). Most cows (16 of 19) treated with two boluses were standing without assistance between 1 and 24 h after treatment and the serum phosphorous was increased to normal levels in five of five tested animals. Study 3 (Ketosis Treatment): cows with clinical ketosis were provided with propylene glycol and K Phos-Boost boluses (n = 29) or only propylene glycol (n = 23). Cows treated with the K Phos-Boost bolus showed a more rapid recovery by increased milk production (3.9 kg/day) and rumination rate (97 min/day). Study 4 (Health Promotion): cows in herds with >40% post-partum hypophosphatemia received K Phos-Boost boluses (n = 130) or no treatment (n = 146) following calving. There was a trend for treated 2nd-lactation animals to have higher milk production after 30 DIM (49.1 vs. 46.2 kg/day; P = 0.09). There were no significant differences between control and bolus treated animals in the incidence of subclinical ketosis, post-calving total health events, or culling rates. The K Phos-Boost bolus is a novel product and has the potential to treat and prevent several important metabolic diseases in dairy cattle. The studies described in this paper are early investigations and further research should be conducted to demonstrate the applications of a dipotassium phosphate bolus in dairy cows.